The Correlation of Vitamin D Concentrations in Healthy Pregnant Women and Their Infants with Outcome Parameters - Jerković Raguž, Marjana; Barišić, Tatjana; Mikulić, Ivanka; Mikulic, Vinka; Šušak, Ivona; Tomic, Vajdana (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
The objective of this prospective study was to assess the concentration and impact of maternal 25(OH)D status on neonatal vitamin D concentrations and early neonatal outcomes in the newborns of mothers who did not take vitamin D supplements during pregnancy. The study is a cohort prospective study of the correlation of VD concentrations in mothers and their newborns. The study included 100 pairs. Only 16 mothers had a VD concentration in the reference interval (75–100 nmol/L), while 84 mothers had values less than 75 nmol/L (p<0.001). A significant difference in maternal VD concentration was determined in relation to tobacco consumption habits during pregnancy and placental condition (p<0.001). 95% of the neonates (95/100) of older, obese multigravida, who had hypovitaminosis D and inadequate exposure to sunshine, had normal VD concentrations (the mean=49.27 nmol/L) on the first day of life. The majority of the mothers gave birth to full-termnewborns with normal vitality scores and CRP and bilirubin levels in the reference interval. The conclusion of this prospective study is that 84% of the healthy pregnant women had hypovitaminosis D. However 95% of their newborns were born full term, with normal anthropometric measurements, normal vitality scores, and normal VD concentrations. This study also confirmed that there is still no cause-and-effect association between hypovitaminosis D in pregnant women and their offspring with outcome parameters for both.
Keywords: infants; pregnancy; hypovitaminosis D; outcome